Effects of nanopatterned-surface dishes on chondrocyte growth and cell cycle progression. Issue 1 (22nd December 2020) - Han, Sang-Soo; Cho, Myung-Ok; Huh, Kang Moo; Kang, Sun-Woong
Abstract : The nanopatterned dish regulated the proliferation rate and cell cycle of chondrocytes. Abstract : Discovering and developing ideal cell culture methods is important for cell biology, drug development, and cell therapy. Recent studies have explored and demonstrated the use of nanoscale structures and patterns that influence cell behavior, such as 3D scaffolds. In this study, we analyzed the effects of nanopatterned-surface dishes using chondrocytes as model cells. Chondrocytes grown on nanopatterned dishes exhibited rounded shapes. Interestingly, chondrocytes have a lower COL10 mRNA level when cultured using nanopatterned dishes. The nanopatterned dishes induced G0-/G1-phase cell cycle arrest and reduced the rate of proliferation. Our results suggest that nanoscale structures can directly control cellular behaviors and can be used for chondrocyte cell culture without causing chondrocytes to lose their functions. These results help to elucidate cellular responses and behaviors in native-like environments, and this information can be used to improve human health.